Detection of wrist movement using EEG signal for brain machine interface - Farid, Ghani, Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2014)
Proceeding of The International Conference on Technology, Informatics, Management, Engineering and Environment 2013 (TIME-E 2013) at Bandung, Indonesia on 23 June 2013 through 26 June 2013.